Non-Linear Storytelling : A Vehicle For Creativity - Mohd Suki, Norbayah (2004)
This research measures the potential of non-linear storytelling in revealing the visual abstraction. The research also concentrates on the level of interactivity , multimedi atechnology convergence, techniques and 3D experimental animation towards users understanding visual abstraction. Three key issues namely distraction, infinite choices and the apparent skills will be discussed to improve and add value towards a better understanding of visual abstraction.